Improving Reading Comprehension Skills of International Elementary School Students through Blended Learning - Olifia Rombot; Endry Boeriswati; M. Atwi Suparman (UIN Siber Syekh Nurjati Cirebon, 2020)
AbstractThis study aims to describe the improvement of elementary school students’ reading comprehension skills through blended learning. The population in this study was all fifth grade students of an international school in Serpong, Tangerang. Using a purposive sampling technique, in total 20 foreign students were involved as a sample in this study. Data were collected using tests and observations and then analyzed using the N-Gain test to see the improvement of students’ reading comprehension skills. Descriptive analysis was also performed to see students’ activities during the learning process. The results showed that the average students’ scores on pre-test and post-test increased by 28 points with an average gain of n-gain of 0.84 in a high category. During the learning process, students also looked happy and enthusiastic in learning Indonesian. Learning Indonesian through blended learning was shown to improve the reading comprehension skills of foreign students. Therefore, blended learning can be used an alternative for solving the problem of limited time and the amount of materials that must be learned, thus giving a positive impact on the reading comprehension skills of foreign students learning Indonesian.Keywords: blended learning, reading comprehension, Indonesian, foreign students. AbstrakPenelitian ini bertujuan untuk mendeskripsikan peningkatan keterampilan membaca pemahaman siswa sekolah dasar melalui pembelajaran blended learning. Populasi dalam penelitian ini adalah seluruh siswa kelas lima suatu sekolah internasional di Serpong, Tangerang. Sementara itu, teknik pengambilan sampel yang digunakan adalah purposive sampling dengan jumlah sampel sebanyak 20 siswa asing. Metode pengumpulan data didasarkan pada tes dan observasi. Data hasil penelitian kemudian dianalisis menggunakan uji N-Gain untuk melihat peningkatan keterampilan membaca pemahaman siswa dan analisis deskriptif untuk melihat aktivitas siswa selama proses pembelajaran. Hasil penelitian menunjukkan bahwa rata-rata pre-test dan post-test meningkat 28 poin dengan perolehan rata-rata n-gain sebesar 0,84 dengan kategori tinggi. Selain itu, selama proses pembelajaran siswa juga terlihat senang dan antusias dalam belajar bahasa Indonesia. Hal berarti bahwa pembelajaran dengan blended learning dapat meningkatkan keterampilan membaca pemahaman siswa asing dalam belajar bahasa Indonesia. Oleh karena itu, pembelajaran dengan blended learning dapat menjadi alternatif dalam menjawab masalah terbatasnya waktu dan banyaknya materi yang harus dipelajari sehingga berdampak pada keterampilan membaca pemahaman siswa asing dalam belajar bahasa Indonesia.Kata kunci: blended learning, pemahaman membaca, bahasa Indonesia, siswa asing.